Determining the Relation of Depression, Anxiety, and Quality of Life with Outcome after Percutaneous Transluminal Coronary Angioplasty - Suprakash Chaudhury; Stuti Saxena; Tahoora Ali; Kalpana Srivastava (Current Innovations in Medicine and Medical Science Vol. 10, 2022)
Background: The advent of Percutaneous Transluminal Coronary Angioplasty (PTCA) was a turning point in the treatment of Coronary Heart Diseases. The psychiatric sequelae of PTCA, though pertinent, have not been sufficiently studied. Methods: Thirty-five patients undergoing PTCA were included in this study. Before the procedure, they filled a proforma constituting sociodemographic details, Hospital Anxiety and Depression Scale (HADS), Coronary Scale, Seattle Angina Questionnaire (SAQ) and a Health-related Quality of Life measure (EQ5D). Three days post-procedure, the patients were once again required to fill HADS, Coronary Scale, SAQ and EQ5D. Results: Significant anxiety and significant depression were present in 46% and 32.1% of the patients before PTCA, respectively. After PTCA, none had significant anxiety, and only 2 (3.6%) patients had significant depression. The SAQ reflected an improvement in physical limitation from 67.9 to 48; in disease perception from 21.2 to 36.1. The EQ5D reflected an improvement in health status from 42.7 to 78.7. Conclusion: PTCA, if successfully done, can result in a significant reduction in anxiety, depression, physical limitation, and can cause an improved health perception and health status.